Perspektif Penetapan Pajak Penambahan Nilai Pada Investasi Aset Kripto Di Era Digital - Saija, Ronald; Labetubun, Muchtar Anshary Hamid (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2023)
In this pandemic era, investment in crypto assets in Indonesia is increasingly attractive as one of the current breakthroughs in digital transactions. Even though crypto prices are very extreme and have a high risk, they are still more attractive to investors to invest in crypto. To be able to anticipate risks in crypto asset trading in Indonesia, the Government has established a regulatory policy on Value Income Tax on crypto asset investments in 2023, in order to reduce the risks of various digital transactions. The research objectives that become a legal gap in this study are: are there government regulations that can reduce the level of risk in digital transactions in crypto asset investments for business actors in Indonesia, and how can the determination of value added tax by the government be able to provide legal certainty for people who use crypto transactions in Indonesia. The research method used in this paper is normative legal research. This research is directed to be able to provide a description of the implications of legal certainty for value income tax in investing in crypto assets through digital transactions, as a policy to prevent risks for business actors. The results of the study show that the optimal regulation of Value Added Tax (VAT) on Crypto Asset Trading is regulated in the Regulation of the Minister of Finance of the Republic of Indonesia Number 68/PMK.03/2022, can reduce the risks that occur, if there are legal issues in the current crypto asset trading. As well as the implications of any profits derived from bitcoin trading activities being reported to the Directorate General of Taxes. Based on Law Number 42 of 2009 concerning the Third Amendment to Law Number 8 of 1983 concerning Value Added Tax on Goods and Services and Sales Tax on Luxury Goods, it includes a Value Added Tax (VAT) of 10%. And the application of legal certainty in the new regulations in the Regulation of the Minister of Finance of the Republic of Indonesia Number 68/PMK.03/2022.